Annuity markets - Cannon, Edmund Stuart, 1969-; Tonks, Ian. (Oxford : Oxford University Press, 2008)
Understanding and tackling the impending pension crisis is a key task for public policy. An annuity protects an individual from outliving their savings, and is central to pensions policy. This title explores the issues surrounding annuities.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Annuities